Question Strategies in Reading Class Posted by English Teacher at UIN Raden Mas Said Surakarta - Verawati, Amanda Ayu; Budiharso, Teguh; Santoso, Rochmat Budi (Institut Penelitian dan Pengembangan Mandalika Indonesia (IP2MI), 2025)
The purpose of this research is to analyze how do question strategies in reading class activate student of 2rd semester at UIN Raden Mas Said Surakarta Researchers used aqualitative approach with design of ethnography. The researcher collected the data by conducting observation, observation field notes, and interview, The participants of this study were teachers who taught in the Reading course in the second semester of the English Language Education Program at UIN Raden Mas Said Surakarta. For the technique of analyzing data, the researcher used Krippendorff theory. The findings reveal that the teacher use 5 types of questions namely Probing questions, this question is most often used by teachers, this type of question emphasizes Students' critical thinking skills. The second is Rephrasing, repeating the previous question with a different language style. then Refocus, returning the focus of students who were previously distracted by other contexts. The fourth is Redirect, encouraging other students to enter the discussion room. And last Reinforcement with the concept (praising students for what they have done or for taking risks in class and participation. In addition, it is also to directly examine how teachers process classes with questioning strategies and student responses to questions that arise.